Dose‐dependent associations between prenatal caffeine consumption and small for gestational age, preterm birth, and reduced birthweight in the Japan Environment and Children's Study. Issue 3 (24th April 2019) - Kobayashi, Sumitaka; Sata, Fumihiro; Murata, Katsuyuki; Saijo, Yasuaki; Araki, Atsuko; Miyashita, Chihiro; Itoh, Sachiko; Minatoya, Machiko; Yamazaki, Keiko; Ait Bamai, Yu; Kishi, Reiko; ,
Abstract: Background: Few previous studies have investigated the association between prenatal caffeine intake and birth size (small for gestational age [SGA], preterm birth, and birthweight Z‐score) in Japan. Objectives: We examined the dose‐dependency of this association (prenatal caffeine consumption and birth size) as part of the Japan Environment and Children's Study. Methods: A prospective birth cohort included 94 876 fetuses in Japan. Participants were enrolled between January 2011 and March 2014. Adjusted multiple linear regression and Cox regression models were used to examine the association between prenatal caffeine levels and infant birth size. Results: The median estimated caffeine consumption during pregnancy was 125.5 mg/day, as determined by self‐administered questionnaires. There were 7252 SGA infants (7.6%) and 4281 preterm birth infants (4.5%). Compared with infants of mothers whose caffeine consumption during pregnancy was in the lowest quartile (4.2 to <86.4 mg/day), infants of mothers whose caffeine consumption was in the highest quartile 4 (205.5‐5080.0 mg/day) were at an increased risk of SGA (relative risk [RR] 1.18, 95% confidence interval [CI] 1.10, 1.27), and at an increased risk of preterm birth at the second trimester of gestation (RR 1.94, 95% CI 1.12, 3.37), with a 0.32‐day reduction in gestational age (95% CI −0.52, −0.12) and with a 0.07 reduction in birthweight Z‐score observed (95% CI −0.09, −0.05). Conclusions: Prenatal caffeine consumption was associated with birth size. However, as the association between prenatal caffeine consumption and birth size was likely confounded by unpredicted potential factors, our confidence in the true causality of the association is moderate.